If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying S = 7r + -33 Reorder the terms: S = -33 + 7r Solving S = -33 + 7r Solving for variable 'S'. Move all terms containing S to the left, all other terms to the right. Simplifying S = -33 + 7r
| 3y-(2x)=5 | | 9(x+4)=8(x-5)+x | | 3b^2-3b= | | 6v+6=2(v-1) | | x+28=52 | | 5+3(x-4)=2(9+1) | | -2(3x-4)+8x-5= | | 2x+x=972 | | -4x^2-10x+3=0 | | x/3+2=x/2 | | 6x+7=2x-3 | | 1.6+x-3.7=-3+5.2 | | 55+4.75w=49.5+4.95w | | 3(d-8)+10= | | 5x-15/6-x=1-x/9 | | 3x+5(x+2)=62 | | 7x-3x+x-5+2x= | | 6x^2-8x+10=0 | | x^2+24xy+144y^2= | | 5g-5-g-5g= | | 3(x+2)+9=3x+8 | | 4+6=-9+7 | | m-7m-3m-5= | | 2+7+x=16 | | -4x^2-9x-4=0 | | 4x+3.2=8.8 | | 5(x-3)+2=3x+2(-5+x) | | 2+(x+4)+8x=8 | | f(x)=-4x^2-9x-4 | | -5-(-30)=x/9 | | -5(4y-6)-y=-2(y-3) | | 4t-8=10 |